Measurement of an elliptic jet - Sai, Tun Leng. (2012)
This project presents an experimental measurement done on the elliptic jet flow across the major y axis of 50mm and minor z axis of 25mm. With the aspect ratio of 2:1, the equivalent diameter of 35.4mm and the corresponding Reynolds number 57805 are used in this experiment.